Relationship Oil Content In The Sediment With An Abudance Of Intertidal Zone Macrozoobenthos Kabung Bay Waters Amid Palm Desert Province Of West Sumatra - Siahaan, Jean Fattikawa; Nedi, Syahrul; Tanjung, Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This research was conducted in October 2015. The study aims to determine the oil content contained in the sediments, abundance of macrozoobenthos in the sediment, and oil content in the sediment relationship and abundance of macrozoobenthos in the Gulf of North West Frontier Kabung method used is survey method, in which the determination of the location established three research stations and each station consists of 6 sampling points. Sediment samples were inserted into the plastic and labeled for chemical laboratory analysis of the fishery. Makrozoobenthos samples given a 10% formalin solution and then brought to the laboratory. Oil content in the sediment at high tide and low tide in the waters of the Gulf Central Kabung ranging from 766.666 to 1166.667 ppm, with the highest oil content was found in station 1 (Port Pertamina) and the lowest at Station 2 (Human Settlements). Type of macrozoobenthos were found in the waters of the Gulf Central Kabung consists of four classes, gastropods, bivalve, crustacean and Polychaeta. Macrozoobenthos species that have a relatively high abundance values at each sampling point the waters of the Gulf Central Kabung namely Alvania lineata. Based on simple linear regression, correlation between oil content with the abundance of macrozoobenthos gained a strong enough relationship, indicated by the value of r = 0.644. Mathematical equation: -0,019x + 41.46 with a coefficient of determination (R2) = 0.414, and has a negative correlation means that the higher the oil content, the abundance of macrozoobenthos lower, though only the remaining 41.42% influenced by other environmental factors.   Keywords: Oil, Sediment, macrozoobenthos